Development and application of a triadic integration teaching model in newly established undergraduate programs: synergistic project-, practice-, and competition-based learning - Sun, Guojin; Wu, Wenbin; Qian, Cairang; Xu, Linqian; Wang, Qi (Frontiers in Education, 2025)
The cultivation of high-quality engineering talent in newly established undergraduate programs presents significant challenges, particularly in integrating theoretical knowledge with practical and innovative capabilities. This study proposes and implements a “triadic integration” teaching model that synergistically combines project-based learning, interactive teaching, and practice-oriented instruction to enhance students’ engineering competencies in a materials innovation course. Project-based learning forms the backbone of the model, guiding students through progressively complex tasks—from foundational to comprehensive and advanced projects—while integrating engineering-material innovation competitions to create a closed-loop “teach–learn–compete” pathway. Interactive teaching strategies, including heuristic, inquiry-based, and participatory methods, foster a student-centered learning ecosystem that enhances engagement, collaboration, and critical thinking. Practice-oriented instruction translates theoretical knowledge into practical application through laboratory experiments, simulation, and full-cycle research projects, cultivating problem-solving and innovation skills in authentic engineering contexts. The model’s effectiveness was evaluated through student performance, competition achievements, and iterative seminar-based reflection among instructors. Results indicate that the triadic approach not only improves students’ technical competence and innovative capacity but also provides a scalable, replicable framework for curriculum innovation in newly established undergraduate programs. This study offers valuable insights for the design and reform of engineering education curricula worldwide.